Semblanza Historiográfica del Monacato Femenino en Toro: El Monasterio Premonstratense de Santa Sofía - Ramos, Lara Arribas (Anuario del Instituto de Estudios Zamoranos 'Florián de Ocampo', 2021)
For some years now, works on medieval female monasticism have witnessed the revitalization of the field, a phenomenon that the cloisters of Toro have also witnessed, unevenly. Here is presented an historiographical sketch of the Norbertine Monastery of Santa Sofia, imbricated with the stages of development of the Hispanic Monastic Studies and the problems derived from a female analysis of the order.
Keywords: toro